Triaxial Creep Behavior of Red Sandstone in Freeze-Thaw Environments. (29th December 2020) - Song, Yongjun; Che, Yongxin; Zhang, Leitao; Ren, Jianxi; Chen, Shaojie; Hu, Mengling
Abstract : To investigate the time-dependent mechanical properties of rock masses in cold regions under the effects of freeze-thaw cycling and long-term loading, triaxial multilevel loading and unloading creep tests were performed on saturated red sandstone samples subjected to different numbers of freeze-thaw cycles. The effects of freeze-thaw cycles and confining pressure on the creep properties, long-term strength, and creep failure mode of the rock were analyzed. The effect of freeze-thaw cycles on the microstructure of the rock was analyzed using scanning electron microscopy. The results showed that as the number of freeze-thaw cycles increased, the rock particle boundaries became more distinct, and more pores formed. The effect of freeze-thaw cycles on the creep deformation of red sandstone was related to the loading stress level. At low stress levels, the rock viscoelastic strain increased gradually and almost linearly with an increasing number of freeze-thaw cycles; in contrast, at high stress levels, the rock viscoelastic strain increased nonlinearly. The viscoplastic strain increased almost linearly with increasing freeze-thaw cycles. The fourth loading stress level (70% σ c ) corresponded to the transition of the creep deformation of the red sandstone. When the confining pressure was low, a higher stress level caused the confining pressure to have a more significant effect on the creep strain. However, as the confining pressure continued to increase, the effect of the confining pressure on the creep strain eventually disappeared. The long-term strength of the red sandstone decreased approximately linearly with an increase in the number of freeze-thaw cycles. When the number of freeze-thaw cycles and the confining pressure were high, the rock samples formed a transverse shear plane and were more fragmented than those without a transverse shear plane. These results provide a reference for construction in rock mass engineering and long-term stability analysis in cold regions.